The Index sAGP is Valuable for Distinguishing Atypical Hepatocellular Carcinoma from Atypical Benign Focal Hepatic Lesions - Luo QQ; Li QN; Cai D; Jiang S; Liu SS; Liu MS; Lv C; Wang JK; Zhang KH; Wang T (Journal of Hepatocellular Carcinoma, 2024)
Qing-Qing Luo,* Qiao-Nan Li,* Dan Cai, Song Jiang, Shao-Song Liu, Mao-Sheng Liu, Cong Lv, Jin-Ke Wang, Kun-He Zhang, Ting Wang Department of Gastroenterology, the First Affiliated Hospital of Nanchang University, Jiangxi Institute of Gastroenterology & Hepatology, Nanchang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ting Wang; Kun-He Zhang, Department of Gastroenterology, the First Affiliated Hospital of Nanchang University, Jiangxi Institute of Gastroenterology & Hepatology, No. 17, Yongwai Zheng Street, Nanchang, Jiangxi, 330006, People’s Republic of China, Tel +86-13361659001 ; +86-13007202818, Email tingwang@ncu.edu.cn; khzhang@ncu.edu.cnPurpose: The differential diagnosis of atypical hepatocellular carcinoma (aHCC) and atypical benign focal hepatic lesions (aBFHL) usually depends on pathology. This study aimed to develop non-invasive approaches based on conventional blood indicators for the differential diagnosis of aHCC and aBFHL.Patients and Methods: Hospitalized patients with pathologically confirmed focal hepatic lesions and their clinical data were retrospectively collected, in which patients with HCC with serum alpha-fetoprotein (AFP) levels of ≤ 200 ng/mL and atypical imaging features were designated as the aHCC group (n = 224), and patients with benign focal hepatic lesions without typical imaging features were designated as the aBFHL group (n = 178). The performance of indexes (both previously reported and newly constructed) derived from conventional blood indicators by four mathematical operations in distinguishing aHCC and aBFHL was evaluated using the receiver operating characteristic (ROC) curve and diagnostic validity metrics.Results: Among ten previously reported derived indexes related to HCC, the index GPR, the ratio of γ-glutamyltransferase (GGT) to platelet (PLT), showed the best performance in distinguishing aHCC from aBFHL with the area under ROC curve (AUROC) of 0.853 (95% CI 0.814– 0.892), but the other indexes were of little value (AUROCs from 0.531 to 0.700). A new derived index, sAGP [(standardized AFP + standardized GGT)/standardized PLT], was developed and exhibited AUROCs of 0.905, 0.894, 0.891, 0.925, and 0.862 in differentiating overall, BCLC stage 0/A, TNM stage I, small, and AFP-negative aHCC from aBFHL, respectively.Conclusion: The sAGP index is an efficient, simple, and practical metric for the non-invasive differentiation of aHCC from aBFHL.Keywords: atypical hepatocellular carcinoma, differential diagnosis, conventional blood indicator, derived index, sAGP